IMPLEMENTASI MODEL KEBIJAKAN PROSPEK: DATA IPH KABUPATEN LOMBOK TIMUR 2024 - KABUL, LALU MUH. (Ganec Swara, 2025)
Focus of the study is implementation model of prospect policy. The study uses a phenomenological approach with qualitative design. The study result showed that prospect policy model is a newest paradigm of public policy implementation. Implementation of prospect policy model in East Lombok Regency in 2024 is supported by price progress index (PPI). Meanwhile, PPI data is published each week by Ministerial Home Affairs through weekly meeting of Regional Inflation Monitoring Team.